Association of Transfusion With Risks of Dementia or Alzheimer’s Disease: A Population-Based Cohort Study - Lin, Shih-Yi; Hsu, Wu-Huei; Lin, Cheng-Chieh; Lin, Cheng-Li; Yeh, Hung-Chieh; Kao, Chia-Hung (Frontiers in Psychiatry, 2019)
Purpose: Association between neurodegenerative diseases and transfusion remained to be investigated. Methods: The study population comprised 63,813 patients who underwent a blood transfusion and 63,813 propensity score-matched controls between 2000 and 2010. Data were obtained from the Taiwan National Health Insurance Research Database, which is maintained by the National Health Research Institutes. A Cox regression analysis was conducted to elucidate the relationship between blood transfusions and the risk of dementia. Results: A multivariate Cox regression analysis of factors, such as age, sex, cardiovascular ischemia disease, and depression, revealed that patients who underwent a blood transfusion showed a 1.73-fold higher risk of dementia [95% confidence interval (CI) = 1.62-1.84] and a 1.37-fold higher risk of Alzheimer disease [95% CI = 1.13-1.66] than those who did not. Patients who received a transfusion of washed red blood cells showed a 2.37-fold higher risk of dementia (95% CI = 1.63-3.44) than those who did not. Conclusion: Blood transfusion, especially transfusion of any type of red blood cells is associated with an increased risk of dementia.